ECOLOGIZATION OF THE HOTEL AND RESTAURANT SECTOR, IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT OF TOURISM IN UKRAINE - PANKIV, Natalia; BYK, Viktoriya (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The paper examines the problems and prospects of greening as an innovative concept of hotel-restaurant development. The current state and trends in the development of greening of tourist infrastructure facilities in Ukraine and the world are analyzed. The criteria and legal principles of eco-hotels have been studied. The main causes and consequences of the negative impact of the hotel-restaurant sector on the environment have been established. The Ukrainian and world experience of existing eco-hotels are characterized, their problems are analyzed and recommendations are made for solving them and for the successful development of eco-hotels in Ukraine. The main tasks that determine effective activity in the eco-hotel business are formulated, in particular: the selection of the most promising target segments of the eco-hotel market and the development of a strategy focused on them; development and formation of ecological style, its correct use in internal and external premises of hotels and restaurants; development of a clear and, in accordance with the requirements of the market, program for the positioning of the eco-hotel; informing consumers through advertising and mass media about the positioning indicators of the eco-hotel and restaurant; development of proposals for the formation and correction of a positive image of the eco-hotel and restaurant in the minds of consumers. It is substantiated that the reorientation of existing hotel enterprises to "environmental" ones can solve several multi-faceted and multi-level tasks at the same time: ensure resource savings at the enterprise level; improve economic indicators due to compliance with the current trend; promote the development of the tourist cluster and the formation of ecological infrastructure in the region; promote the ideas of a "green" way of life in society; to form the market of ecological products and services; improve the image of the region and the country. Based on the results of the research, the following advantages of eco-hotels are highlighted: conservation of natural resources; reduction of water consumption; saving electricity; reduction of costs for energy resources; reduction of costs for materials undergoing secondary processing; attracting new customers due to a favorable environmental situation; positive positioning of the services market; additional opportunity to advertise the hotel; creating a reputation for the brand and the hotel as a socially responsible company. Positioning the hotel as an eco-hotel gives its owner a number of competitive advantages, among which the possibility of using this status for advertising purposes, creating a favorable microclimate for staff and guests, and increasing occupancy rates should be highlighted. It is well-founded that eco-hotels are promising hotels that are designed to maintain the state of the natural environment, raise environmental awareness and responsibility in society, and their guests can enjoy a healthy vacation in harmony with nature.